(untitled) - Dobrotkova, Marta (Doprava a spoje, 2010)
Transport of the perishable foodstuffs is one of the specialized transport, which is required fulfillment of certain conditions .ATP agreement govers these conditions. On the basis of ATP milk includes amoung perishable foodstuffs. There are mentioned conditions that the carrier must comply for this transport in this article